Race and Resurrection: Contesting Colorblind White Supremacy with Biblical Resources. Issue 1 (April 2020) - Norris, Kristopher
This essay argues that Paul's discourses in 1 Corinthians 12 and 15 concerning the church as the Body of Christ and the resurrection of the body offer a biblical challenge to colorblind white supremacy when read in conversation with feminist and womanist theologians. Reading Paul through feminist and womanist treatments of the body and trauma provides a nuanced theology of the body and a complex account of the concrete wounds of white supremacy while also presenting theological and ethical resources for resisting colorblindness.